Swine cysticercosis and associated risk factors in non-technified pig breeding in semi-arid region of Sergipe state, Brazil - Marinho, Glenda Lídice de O. C.; Schwarz, David Germano G.; Trigo, Beatriz B. [UNESP]; Nunes, Caris M. [UNESP]; Romeiro, Edenilze T.; de Azevedo, Edisio O.; da Silva, José Eduardo M.; Farias, Márcia Paula O.; Oliveira, Juliana F.; Faustino, Maria Aparecida da G. (Springer Nature, 2021)
The aim of this study was to determine the frequency of Taenia solium anti-metacestode antibodies in slaughtered pigs in a semi-arid region of the “Alto Sertão” of Sergipe state, Brazil, and verify the risk factors associated with swine cysticercosis. For this, 230 samples of swine blood from two slaughterhouses were collected and analyzed by indirect ELISA. The pigs came from five non-technical properties in the semi-arid region of the Alto Sertão of Sergipe state. Searches for cysts in the skeletal muscles of the pigs were performed during slaughter. In addition, an epidemiological questionnaire was applied to the pigs’ original properties to determine risk factors. Besides that, the official health services database was evaluated for confirmed cases of neurocysticercosis and taeniasis in humans in the last 5 years, living in the studied region. Seropositivity in pigs was 12.6%, with no significant difference between males and females. No cysts were found in the carcasses of the slaughtered pigs. A positive association was found for properties that discharge domestic sewage into the environment, in river or streams, increasing the risk of positivity by 5.72 times. When analyzing the database of official agencies, there were no records of cases of neurocysticercosis or taeniasis in the resident population in the last 5 years. However, there were frequent cases of idiopathic epilepsy. The results demonstrate that study area is endemic for swine cysticercosis and serves as a warning of the possibility of the occurrence of the taeniasis-cysticercosis complex.
Keywords: Cysticercus cellulosae; ELISA; Epidemiology; Taenia solium